Rural labor migration, characteristics, and employment patterns: a study based on China's agricultural census - Tuan, Francis; Somwaru, Agapi; Diao, Xinshen (China Statistics Press, 2002)
This study examines the rural labor market in China exclusively based on China's first national agricultural census. The authors analyze the demographic characteristics of the rural labor force and their association with the type of employment, place of work, and labor migration. They then investigate demographic distributions of rural labor force in order to capture their relation with the distribution of other resources especially land availability or land constraints. Finally, they appliy a generalized polytomous logit technique to analyze the patterns of rural labor employment and forecast rural migration. In this framework, they atempt to relate rural labor migration with demographic characteristics, types of occupation, place of work, geographic characteristics, and various economic development indicators.